Santa Anita, California Assembly Center. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows a portion of the completed Santa Anita, California Assembly Center, situated within the race track at Arcadia, California.